2020
DOI: 10.3389/fonc.2020.00796
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hypoxia Signature to Evaluate the Tumor Immune Microenvironment and Predict Prognosis in Glioma Groups

Abstract: Glioma groups, including lower-grade glioma (LGG) and glioblastoma multiforme (GBM), are the most common primary brain tumor. Malignant gliomas, especially glioblastomas, are associated with a dismal prognosis. Hypoxia is a driver of the malignant phenotype in glioma groups; it triggers a cascade of immunosuppressive processes and malignant cellular responses (tumor progression, anti-apoptosis, and resistance to chemoradiotherapy), which result in disease progression and poor prognosis. However, approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 35 publications
(34 reference statements)
2
156
0
Order By: Relevance
“…Herein, we further explored the role of hypoxia in the tumor immune microenvironment. Accumulating evidence indicates that hypoxia may protect tumors from immune responses through various mechanisms, including by inhibition of NK and CTL cell activity, promotion of immunosuppressive cytokines, and by enhancing immunosuppressive cells (T reg cells, TAMs, and neutrophils) (139).…”
Section: Hypoxia In the Glioblastoma Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we further explored the role of hypoxia in the tumor immune microenvironment. Accumulating evidence indicates that hypoxia may protect tumors from immune responses through various mechanisms, including by inhibition of NK and CTL cell activity, promotion of immunosuppressive cytokines, and by enhancing immunosuppressive cells (T reg cells, TAMs, and neutrophils) (139).…”
Section: Hypoxia In the Glioblastoma Microenvironmentmentioning
confidence: 99%
“…Hypoxia can cause a prolonged reduction in IL-2 mRNA expression and inhibit NK cell and CTL activity. Meanwhile, hypoxia has also been shown to reduce the ability of NK cells to release IFNg, TNFa, GM-CSF, CCL3, and CCL5 (139,141). In patients with a high risk of hypoxia, CTLs and NK cells appeared to be in resting status rather than active (139), revealing that hypoxia might lead to a state of immune suppression.…”
Section: Ctls and Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between hypoxia and immune suppression in the TME is well established and is strongly linked to numerous mechanisms described above, including the impairment of IFN-I signalling, upregulation of immune checkpoint molecules and the upregulation of extracellular adenosine [ 170 ]. Elevated hypoxic gene signatures are a major prognostic indicator in cancer patients and are frequently associated with immune-privileged (‘cold’) tumour niches [ 171 , 172 ]. Hypoxia and the induction of lactate metabolism has been reported to promote M2 polarisation of TAMs via the activation of HIF-1, Hedgehog and mTOR pathways [ 173 , 174 ].…”
Section: Hypoxiamentioning
confidence: 99%
“…For example, microglia of the retina preserve a CD45 low phenotype in a light injury model and could be discriminated from infiltrating macrophages [ 74 ], while microglia of the spinal cord increased CD45 expression in a demyelination model [ 75 ]. Notably, it was demonstrated that myeloid cells showed increased expression and activity of CD45 if cells were exposed to hypoxia [ 76 ] while hypoxia is a hallmark of glioma [ 77 , 78 ]. Especially in the brain tumor context, our group clearly demonstrated a contribution of microglia to the CD45 high population in vivo, if gliomas in chimeric mice generated by head-protected irradiation were investigated [ 79 ].…”
Section: Distinction Of Microglia and Macrophages In Gliomamentioning
confidence: 99%